Politics in theology - Ricci, Gabriel R., 1948- (New Brunswick, N.J. : Transaction Publishers, 2012)
This volume examines the relationship between religion and politics from a historical perspective. Contributors address specific moments in which political governance intersects with religious ideals in dramatic ways. These moments question the relationship between religious sentiments and political solutions and threaten to reorder the geopolitical landscape. These essays discuss the tensions produced by secularism in an Islamic culture, the influence of Catholic theology in workers' political movements, and how Hinduism has been transformed by the political process. Also featured are essays that emphasize how civil religion coincides with constitutional order, and how the drama of religious tolerance and legitimization of the power of Christian hierarchy originated in the political power of the Roman emperor.
Includes bibliographical references.
Keywords: Religion and politics; Religion and politics -- History